Selenophenes: Introducing a New Element into the Core of Non‐Steroidal Estrogen Receptor Ligands. (9th January 2017) - Zhang, Silong; Wang, Zhiyong; Hu, Zhiye; Li, Changhao; Tang, Chu; Carlson, Kathryn E.; Luo, Junjie; Dong, Chune; Katzenellenbogen, John A.; Huang, Jian; Zhou, Hai‐Bing
Abstract: The importance of the heterocyclic core elements with peripheral phenolic and alkyl substituents as a dominant structural motif of ligands for the estrogen receptor (ER) has been well recognized. In this study we expanded the structural diversity of core elements by preparing selenium‐containing heterocycles and exploring the activities of these selenophenes on the two ERs, ERα and ERβ. Careful structure–activity relationship (SAR) analysis of their ER binding affinities showed that most selenophenes are ERβ‐selective, with the position of the phenol substituents on the selenophene core and the nature of these substituents having a marked effect on their binding affinities. The compound bis(2‐fluoro‐4‐hydroxyphenyl)selenophene (2 f ) has the highest relative binding affinity (RBA) of 24.3 for ERβ. In transcription assays, most selenophenes were found to exhibit partial to full agonist activity for both ER subtypes, with compounds bis(2‐methyl‐4‐hydroxyphenyl)selenophene (2 b ), bis(4‐fluoro‐3‐hydroxyphenyl)3‐bromoselenophene (6 f ), and 2, 3, 5‐tris(hydroxyphenyl)thiophenes (8 b and8 d ) profiling as superagonists for ERα; however, several compounds display a range of ERα or ERβ antagonistic activities. A few selenophenes exhibited antiproliferative activity, with compound8 c showing antiproliferative effects similar to that of 4‐hydroxytamoxifen in breast cancer MCF‐7 cells while being nontoxic to normal VERO cells. These new ligands could act as models for the development of novel agents leading to improved therapeutics that target the estrogen receptor. Abstract : Add a new element ! This is the first report of selenophene‐core compounds as estrogen receptor (ER) ligands. In transcription assays, several selenophenes were profiled as superagonists for ERα; moreover, a few selenophenes exhibited antiproliferative activity similar to that of 4‐hydroxytamoxifen in MCF‐7 breast cancer cells while being nontoxic toward normal VERO cells. These new ligands could act as models for the development of novel agents leading to improved therapeutics that target the ER.